Tellurium Vanadate Glasses: V4+colorimetric Measure and Its Effect on Conductivity - McDonald, Lisa; Siligardi, Cristina; Vacchi, Marco; Zieser, Adam; Affatigato, Mario (Frontiers in Materials, 2020)
This research comes as part of a broader resurgence of study of the electrical conductivity of glasses—and the mechanism for electronic motion in the amorphous network—spurred by newfound interest in using glasses in detectors for particle physics and medical applications, taking advantage of the glasses’ tailorable conductivity, chemical durability, and mechanical strength. The work presented in this study regards the preparation and the characterization of some binary glasses belonging to the TeO2-V2O5 system. In particular we focused the attention on their electrical conductivity at room temperature and at higher temperature as a function of the V4+ ions content into the glass structure. The amount of V4+ into the glass was obtained by a colorimetric method. Moreover density, thermal properties (Tg, Cp), as well as and SEM and XRD measurements were also performed.